Potential interactions between uraemic toxins and drugs: an application in kidney transplant recipients treated with calcineurin inhibitors. Issue 11 (30th March 2021) - André, Camille; Choukroun, Gabriel; Bennis, Youssef; Kamel, Said; Lemaire-Hurtel, Anne Sophie; Masmoudi, Kamel; Bodeau, Sandra; Liabeuf, Sophie
Abstract: Background: The uraemic toxins that accumulate as renal function deteriorates can potentially affect drug pharmacokinetics. This study's objective was to determine whether plasma concentrations of certain uraemic toxins are correlated with blood concentrations of two immunosuppressants. Methods: DRUGTOX was a cross-sectional study of 403 adult patients followed up after kidney transplantation and who had undergone therapeutic drug monitoring (TDM) of calcineurin inhibitors (tacrolimus or cyclosporin) between August 2019 and March 2020. For each patient, immunosuppressant trough concentrations (C0 ) were measured in whole blood samples and then normalized against the total daily dose (C0 :D ratio). The sample was assayed for five uraemic toxins [urea, trimethylamine N-oxide (TMAO), indole acetic acid (IAA), p -cresylsulphate (PCS) and indoxylsulphate (IxS)] using liquid chromatography–tandem mass spectrometry. Results: The median age was 56 years [interquartile range (IQR) 48–66] and the median estimated glomerular filtration rate was 41 mL/min/1.73 m 2 (IQR 30–57). Age, sex, body mass index (BMI), urea, IxS and PCS were significantly associated with an increment in the tacrolimus C0 :D ratio. A multivariate analysis revealed an independent association with IxS [odds ratio 1.36 (95% confidence interval 1.00–1.85)] after adjustment for sex, age and BMI, whereas adjustment for age weakened the association for PCS and urea. In a univariate logistic analysis, age, sex, BMI and the TMAO level (but not PCS, IxS, IAA or urea) were significantly associated with an increment in the cyclosporine C0 :D ratio. Conclusions: Even though TDM and dose adaptation of immunosuppressants keep levels within the therapeutic window, increased exposure to tacrolimus (but not cyclosporine) is associated with an accumulation of PCS, IxS and urea.